2016
DOI: 10.1002/14651858.cd006107.pub4
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound versus 'clinical touch' for catheter guidance during embryo transfer in women

Abstract: This review is published as a Cochrane Review in the Cochrane Database of Systematic Reviews 2016, Issue 3. Cochrane Reviews are regularly updated as new evidence emerges and in response to comments and criticisms, and the Cochrane Database of Systematic Reviews should be consulted for the most recent version of the Review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 61 publications
0
14
0
2
Order By: Relevance
“…In the last few years of the study period, the CS-group had an echogenic catheter and ultrasound for the embryo transfer, as shown in Table 1. Currently there is little evidence that ultrasound-guided embryo transfer improves pregnancy outcomes (Brown, Buckingham, Abou-Setta, & Buckett, 2010;Brown, Buckingham, Buckett, & Abou-Setta, 2016). Separate analysis of live birth rate did not show a significant difference between the two periods (data not shown).…”
Section: Discussionmentioning
confidence: 89%
“…In the last few years of the study period, the CS-group had an echogenic catheter and ultrasound for the embryo transfer, as shown in Table 1. Currently there is little evidence that ultrasound-guided embryo transfer improves pregnancy outcomes (Brown, Buckingham, Abou-Setta, & Buckett, 2010;Brown, Buckingham, Buckett, & Abou-Setta, 2016). Separate analysis of live birth rate did not show a significant difference between the two periods (data not shown).…”
Section: Discussionmentioning
confidence: 89%
“…In our study, the clinical pregnancy rate was the same in both groups, and using transabdominal ultrasound for insemination provided no added benefits to the clinicians or patients. For embryo transfer in IVF, ultrasound guidance leads to an increase in the pregnancy and live birth rates [11]. In IVF, the cervical and uterine manipulations during catheterization can induce contractions and endometrial trauma that may lead to expulsion of the embryo [15-17].…”
Section: Discussionmentioning
confidence: 99%
“…The majority of published studies on IUI have focused on ovarian stimulation and seminal fluid parameters, instead of on the technique of insemination itself [10]. For IVF procedures, in 2016, the Cochrane Database of Systematic Reviews presented an analysis of 21 RCTs comparing ultrasound guidance during embryo transfer versus the blind method, which relies on the clinician’s tactile senses to judge if the catheter is in the correct position, and concluded that ultrasound guidance led to higher clinical pregnancy rates and live birth rates than the blind method of embryo transfer [11]. Therefore, we sought to determine whether the same technique using transabdominal ultrasound guidance during intrauterine catheter insemination (US-IUI), compared to the blind method IUI without ultrasound guidance (BM-IUI), improved clinical pregnancy rates in IUI treatment cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Among the most important variables that determine the success or failure of the procedure are: ultrasound guidance ( Brown et al , 2016 ), uterine contractions during ET ( Pierzyński & Zbucka-Kretowska, 2014 ), and the catheter type used during the procedure ( Buckett, 2006 ). A few years ago, the type of catheter chosen was recognized as one of the main variables interfering positively or negatively on the ET effectiveness.…”
Section: Introductionmentioning
confidence: 99%